Réponses

2014-01-09T10:16:09+01:00
D = 3/5 - 7/3 + -3/2
D = 9/15 - 35/15 + -3/2
D = -26/15 + -3/2
D = -52/30 + -45/30
D = -97/30
D = 97/-30

E = (-7/1 - 1/4) x 8/3
E = (-28/4 - 1/4) x 8/3
E = -29/4 x 8/3
E = -232/12
E = 58/-3

F = -7/4 - 1/4 x 8/3
F = -8/4 x 8/3
F = -64/12
F = 16/-3

H = -3/7 x (-21/8) x 4/-3
H = 63/56 x 4/-3
H = 9/8 x 4/-3
H = 36/-24
H = 3/-2

I = 2/5 + 1/3
     2/3 - 1/2
I = 6/15 + 5/15
     4/6 - 3/6
I = 11/15
      1/6
Maudmarine, il n'y aurait pas une petite erreur dans le dernier?
2014-01-09T10:38:47+01:00
D = 3/5 - 7/3 + -3/2=
9/15 - 35/15  -3/2 =
-26/15 -3/2=
-52/30 - 45/30=
D = -97/30

E = (-7/4 - 1/4) x 8/3=
(-28/4 - 1/4) x 8/3=
-29/4 x 8/3=
-232/12=
E = -58/3

F = (-7/4 - 1/4) x 8/3=
-8/4 x 8/3=
-64/12=
F = -16/3

H = -3/7 x (-21/8) x 4/-3=
63/56 x 4/-3=
9/8 x 4/-3=
-36/24=
H = -3/2

I = (2/5 - 1/3)/( 2/3 - 1/2) =
(6/15 -5/15)/(4/6-3/6)=
1/15 *6=
6/15=
I = 2/5